Analysis of Papers Physical Properties Made from Mixing LbL-treated and Refined Pulp by Response Surface Method - Hamid reza Rudi (Regional Information Center for Science and Technology (RICeST), 2016)
In this study, the effect of using Layer-by-Layer (LbL) treated pulp as mixed with refined OCC recycled pulp was investigated on paper physical properties. The LbL treatments were conducted to build 7 consecutive cationic and anionic starch layers. Afterwards, at three levels of 10, 20 and 30 percent, LbL-treated pulp was added to the 10, 15 and 20 minutes refined pulp. From mixed pulp, handsheets with basis weight of 60 g/m2 were prepared and its physical properties including: thickness, density, roughness and formation was examined. The results of LbL treatment using AFM micrographs indicated that the surface of fibers was covered with starch polymer particles by means of Layer-by-Layer treatment. Also, SEM micrographs confirm starch impregnated fibers surface and formation of rough surfaces. Analysis mutual effect of independent variables revealed that addition of LbL-treated pulp to the refined recycled pulp had only significant effect on paper thickness and surface roughness, while variation of refining time had significant influence on all physical properties. In current research, considering the results of ANOVA test and the mutual effect of the content of LbL-treated pulp and different refining time levels on the paper physical properties using response surface methodology, adding of 10 % of LbL-treated pulp to the OCC pulp and applying the refining time of about 18.66 minutes was selected as optimum condition.